1975
DOI: 10.2134/agronj1975.00021962006700030030x
|View full text |Cite
|
Sign up to set email alerts
|

Time of N Application and Yields of Corn in Wet, Alluvial Soils1

Abstract: Time and rates of N application to corn (Zea mays L.) grown in wet alluvial soils in western Kentucky were studied in the years 1968 through 1972. Two soils representative of the wetter soils in the area were used, Stendal silt loam and Melvin silt loam. The objective of the study was to determine the N fertilization practices that would produce highest corn yields on such soils. The early experiments were concerned with Fall vs. Spring application of N as practiced in the Midwest, but Fall‐applied N at lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
2
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 0 publications
4
26
2
1
Order By: Relevance
“…Yield was maximized at 1200 and 1590 g m -2 for the 2011 and 2012 growing seasons, respectively. Previous research has indicated that split-N applications, especially those including in-season N applications can significantly affect NUE and corn grain yield (Miller et al, 1975;Olson et al, 1986). During 2011, there were no statistical differences among treatments involving the optimal-N rate applied in a three-way split and any of the suboptimal-N rates and timing combinations although they were significantly less than the optimal-N rate applied in a two-way split.…”
Section: Corn Grain Yieldmentioning
confidence: 76%
See 1 more Smart Citation
“…Yield was maximized at 1200 and 1590 g m -2 for the 2011 and 2012 growing seasons, respectively. Previous research has indicated that split-N applications, especially those including in-season N applications can significantly affect NUE and corn grain yield (Miller et al, 1975;Olson et al, 1986). During 2011, there were no statistical differences among treatments involving the optimal-N rate applied in a three-way split and any of the suboptimal-N rates and timing combinations although they were significantly less than the optimal-N rate applied in a two-way split.…”
Section: Corn Grain Yieldmentioning
confidence: 76%
“…Work conducted by Russelle et al (1981) and Welch et al (1971) indicated that NUE in corn could be greatly improved simply by applying fertilizer-N as close to the growth stage of peak N demand as possible. Delayed application of N in-season, when corn N demand is high, can greatly infl uence NUE as well as corn grain yield (Miller et al, 1975). Although delaying N applications in corn can lead to greater NUE and potential for increased yields, work by Scharf et al (2002) indicated that there was a distinct cut-off (V12) for applying the season-total N rate in a single application with little to no yield loss.…”
mentioning
confidence: 99%
“…Efficiency of use from a single pre-plant N-fertilizer application typically decreases in proportion to the amount of N fertilizer applied (Reddy and Reddy, 1993). Other studies have substantiated that in-season applied N resulted in a higher NUE than when N is pre-plant applied (Miller et al, 1975;Olson et al, 1986;Welch et al, 1971;Randall et al, 2003a,b). Collectively, these results agree with the recommendations of Keeney (1982), who advocated that the most logical approach to increasing NUE is to supply N as it is needed by the crop.…”
Section: Causes Of Low Nue For Current N Management Strategiesmentioning
confidence: 98%
“…Aldrich (1984), Olson and Kurtz (1982), Russelle et al (1981), Stanley and Rhoads (1977), and Welch et al (1971) all agree that the best practice in managing maize is the application of N fertilizer at the time (or near the time) when both the need for N and N uptake are maximum for maize plants because it promotes higher NUE by reducing denitrification, N immobilization and leaching. Miller et al (1975) and Olson et al (1986) evaluated the efficiency of in-season N application and concluded that both NUE and grain yields can be increased by delaying N fertilization for maize. Results of a seven-year study on timing of N application in maize and soybean production, conducted by Randall et al (2003), demonstrated lowest grain yields were achieved with fall N application compared to highest grain yields with split N fertilization.…”
Section: Introductionmentioning
confidence: 99%